Alegoria Distópica da Contemporaneidade e Biopolítica em The Childhood of Jesus (2013), de J.M. Coetzee - Barbosa, Cidália (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
The first novel The Childhood of Jesus (2013) from the last trilogy published by JM Coetzee, followed by The Schooldays of Jesus (2016) and The Death of Jesus (2019), inaugurates a dystopian and purposefully organized ―New World‖ by creating an atmosphere of control from government institutions in this country. As a result, the narrative suggests a democracy that functions in a regulated manner and which relates in a similar way to contemporary times. The purpose of this article is to analyze how dystopia and biopolitics are present in the novel and how, based on these concepts, an allegory is made in relation to contemporaneity. It follows closely the definitions of ―dystopia‖ and ―ustopia‖ through Jacoby (2000) and Atwood (2011) and of ―biopolitics‖ through Foucalt (1979).